2009
DOI: 10.1097/sla.0b013e3181b21c7b
|View full text |Cite
|
Sign up to set email alerts
|

Signet Ring Cell Histology is an Independent Predictor of Poor Prognosis in Gastric Adenocarcinoma Regardless of Tumoral Clinical Presentation

Abstract: This study is currently the best evidence showing that SRC is a major and independent predictor of poor prognosis due to specific characteristics such as more infiltrating tumors showing affinity for lymphatic tissue accompanied by a higher rate of peritoneal carcinomatosis. Our results suggest the need for a specific therapeutic strategy for such tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
221
1
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(254 citation statements)
references
References 35 publications
16
221
1
16
Order By: Relevance
“…The prognostic significance of older age and histological type in our study is comparable to the results of other studies [13,20,21]. The prognosis was significantly better for lymphoma than for adenocarcinoma, and prognosis was worse for undifferentiated carcinoma than for adenocarcinoma.…”
Section: Discussionsupporting
confidence: 81%
“…The prognostic significance of older age and histological type in our study is comparable to the results of other studies [13,20,21]. The prognosis was significantly better for lymphoma than for adenocarcinoma, and prognosis was worse for undifferentiated carcinoma than for adenocarcinoma.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies reported better 5-year survival rates in SRC than in other cell types [1,2]. However, others reported no significant differences [3] or a poorer prognosis [4][5][6]. In addition, studies that compared SRC with the other cell types in early gastric cancer (EGC) found that SRC had lower lymph node metastasis with better prognosis than other cell types and suggested endoscopic resection for the treatment of signet ring cell-type EGC patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, many reports regarding the clinical importance of a positive margin did not describe the method of evaluation of the true surgical margin or the most appropriate device to dissect the tissue. Although a positive margin has often been associated with poor prognosis in gastric cancer [5][6][7][8], it has lost prognostic relevance in some specific cohorts [9][10][11]. Besides the biological characteristics of these specific cohorts, inaccurate handling of the surgical margin for histologic evaluation may have led to these conflicting results.…”
Section: Discussionmentioning
confidence: 84%